The Exercise Promotion Model for Students of Lampang Vocational College - ไชยจักร, ณัฐภัทร์; ตรีโสภณากร, ขจร; ลี่ทองอิน, พรเทพ (Journal of Graduate Research, 2019)
The purpose of this research was to study the needs of exercise promotion, to construct and evaluate the exercise promotion model for students at Lampang Vocational College. The sample group used in this research consisted of 400 students who studied in the first semester of the 2019 academic year and the administrators at Lampang Vocational College. The research instruments were the 5-level-rating scale questionnaire on the need for exercise promotion, an interview, a focus group discussion and a model evaluation form. The data were analyzed for percentage, mean, standard deviation and content analysis The research found that 1) The need to promote the exercise of the students - students was at the highest level (x ̅= 4.30, SD = 0.29) 2) The form of exercise promotion of the students consisted of seven aspects: strategy, structure, form, personnel system, shared values. 3) The model assessment results revealed that the model was accurate (x ̅= 4.74, S.D. = 0.37), appropriate (x ̅= 4.78, S.D. = 0.06), feasible (x ̅= 4.70, S.D. = 0.04) and utilizable (x ̅= 4.74, S.D. = 0.04)